Mothers' Sources and Strategies for Managing COVID-19 Uncertainties during the Early Pandemic Months. Issue 3 (3rd July 2021) - Walker, Kimberly K.; Head, Katharine J.; Bute, Jennifer; Owens, Heather; Zimet, Gregory D.
ABSTRACT: The COVID-19 pandemic presents unprecedented challenges and uncertainties for families. Guided by uncertainty management theory, this study qualitatively explored mothers' sources of COVID-related uncertainties for their older children and the strategies used to manage their uncertainties. Twenty-five mothers in the U.S. Midwest were interviewed by telephone between March-May 2020 during the early pandemic months. Data indicated four sources of uncertainty: adjustment, threat of COVID-19, COVID-19 information, and social interaction. Protective behaviors used to manage threat of COVID-19 uncertainties (e.g., social distancing and isolation) sometimes unleashed further uncertainties about social interactions with others that mothers were still attempting to manage. The findings suggest theoretical implications of uncertainty management theory as it applies to COVID-19 and practical implications for empowering mothers with tools for support and health literacy skills to understand and act on credible COVID-19 information.